Kajian Langgam Pada Bangunan Masjid Raya Bogor - Irvan Maulana; Diana Susilowati (Universitas Medan Area, 2023)
The mosque is a place of worship for the Muslim community which has the capacity for a large number of congregations, over time the mosque is not only a place of worship but the mosque can also be a place for socializing in religious matters, in every city and region it has its own characteristics regarding the design and style that is in the mosque. The style of a marker or pattern on a building based on a certain period is usually the style of the mosque found on the exterior and interior of the building such as the shape of the door, the shape of the column, the shape of the roof, the shape of the ceiling and so on. The research method used in this research is descriptive qualitative by searching and collecting data related to research from journals, literature, books and direct surveys to research locations. The results of the research are knowledge of what styles exist in the Al-Mi'raj mosque (Masjid Raya Bogor) and find out which form of mosque design follows.